SPAG5 Is Involved in Human Gliomagenesis Through the Regulation of Cell Proliferation and Apoptosis - Wang, Chunhong; Su, Haiyang; Cheng, Rui; Ji, Hongming (Frontiers in Oncology, 2021)
Background Glioma is the most frequent malignant primary brain tumor in adults. Objective To explore the role of sperm-associated antigen 5 (SPAG5) in glioma. Methods The association between SPAG5 expression and clinical features was investigated based on The Cancer Genome Atlas (TCGA) datasets. The function of SPAG5 in glioma was analyzed using U87 and U251 cells. Knockdown glioma cells were constructed by shRNA interference. qRT-PCR and Western blotting were used to measure the expression of SPAG5 and Cadherin 2 (CDH2). Cell proliferation and apoptosis were measured by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, caspase 3/7 assay, and high-content screening (HCS) proliferation analysis and colony formation assay. Transwell assays and wound-healing assays were used to investigate cell migration and invasion. Results The increased expression of SPAG5 was correlated with poor outcomes in glioma patients. Knocking down SPAG5 could inhibit the proliferation and colony formation and promoted the apoptosis of glioma cells. Knocking down SPAG5 could also inhibit cell migration and invasion and the expression of CDH2. Overexpression of CDH2 with SPAG5 depletion could restore the proliferation and inhibit the apoptosis of glioma cells, which also promoted cell migration and invasion. Conclusions SPAG5 is a promising prognostic factor and potential therapeutic target for clinical intervention in glioma.